2019
DOI: 10.1155/2019/5328238
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Potential of Aloe weloensis (Aloeacea) Leaf Latex against Gram-Positive and Gram-Negative Bacteria Strains

Abstract: Objective To evaluate the antibacterial effects of the leaf latex of Aloe weloensis against infectious bacterial strains. Methods The leaf latex of A. weloensis at different concentrations (400, 500, and 600 mg/ml) was evaluated for antibacterial activities using the disc diffusion method against some Gram-negative species such as Escherichia coli (ATCC 14700) and Pseudomonas aeruginosa (ATCC 35619) and Gram-positive such as Staphylococcus aureus (ATCC 50080) and Enterococcus fecalis (ATCC 4623). Results The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…The sap was, then, left in open air for three days to allow evaporation of water, which yielded a pale yellow latex. Finally, after drying, the dried latex was transferred into a vial and, then, kept in a refrigerator until further use [ 13 – 15 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sap was, then, left in open air for three days to allow evaporation of water, which yielded a pale yellow latex. Finally, after drying, the dried latex was transferred into a vial and, then, kept in a refrigerator until further use [ 13 – 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…weloensis (Eret tafa) is traditionally used for the treatment of malaria, wound, different skin diseases and pain from ear infection, headache, and rheumatism. An ethnobotanical survey conducted in Gubalafto, Northeast Ethiopia, reported that the leaf latex of the plant is taken orally to treat malaria [ 12 , 13 ]. However; the antimalarial activity of this medicinal plant is not scientifically studied.…”
Section: Introductionmentioning
confidence: 99%
“…Between 1981 and 2014, 43.6% of anti-infective drugs were approved and 40.7% of anticancer agents were based on natural products or derivatives thereof [ 22 ], and many natural products have become a template for drug design because they often present a ligand–protein binding motif [ 23 ]. Some natural products have shown antibacterial activity like as described by Nofiani et al [ 24 ] and Emiru et al [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…They have been demonstrated antibacterial, antitumor, antiin ammatory, anti-arthritic, anti-rheumatoid, anticancer and antidiabetic activities (16). The latex of Aloe weloensis leaf showed antibacterial effect against gram negative and gram positive strains (17). The leaf latex of the plant has been used in folk medicine against malarial and others human ailment in Ethiopia (18).The leaf latex and isolated compounds of Aloe vera, Aloe pulcherrima and Aloe megalacantha, a similar plant species, possessed signi cant antimalarial activity (19)(20)(21).As a result, Aloe weloensis may have similar effect as all plants belong to the same genus.…”
Section: Introductionmentioning
confidence: 99%